SISTEM INFORMASI PEMASARAN PERUMAHAN GRIYA PANJI BERBASIS WEB PADA PT NOVAL PERKASA PRIMA - Anita Kusumasari; Dedi Haryanto; Muhammad Ihsan (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2024)
The continuous population growth in Indonesia has spurred a surge in housing demand, which is not only a basic necessity but also a symbol of social and economic status. To meet this demand, Home Ownership Credit (KPR) serves as an important financing instrument, facilitating the community in purchasing or renovating homes. PT. Noval Perkasa, a private company engaged in housing project development, faces challenges in marketing the Griya Panji housing project, which still relies on conventional methods such as brochures and manual record-keeping. This research designs a web-based marketing information system to simplify the promotion and ordering process of homes in real-time. The website allows potential buyers to access comprehensive information about housing and conduct transactions without having to visit the site, while management can monitor and evaluate the data on housing down payment orders for strategic decision-making. The results of this study are expected to assist PT. Noval Perkasa in managing housing marketing more efficiently and modernly, as well as attract more potential buyers.